AN EXPLANATORY MODEL OF DE ATTITUDE TOWARD IMMIGRANTS IN THE REGION OF MURCIA (SPAIN) - Ramírez de la Fe, Mª del Carmen; Rodríguez González, Ángel (Anales de Psicología / Annals of Psychology, 2006)
This study analyses the relation between some psychosocial variables and the attitudes of Murcian people toward immigrants. Ninety three secondary-school students answered some measurement tools about the following variables: outgroup similarity to the ingroup, contact with outgroup members (presence contact and personal interaction), outgroup stereotype (stereotype valence and stereotype extent), perception of outgroup social contribution, and emotions generated by the outgroup (posi-tive and negative). A multiple regression analysis shows a R2 = .81, including the following variables in the model: similarity to the ingroup, perceived social contribution, positive emotions, personal interaction and stereotype valence. Results point out the usefulness of these variables for explaining the attitude toward immigrants in the Region of Murcia.